Promoting Paraeducators' Use of Evidence-Based Practices for Students With Autism. (April 2023) - Sam, Ann M.; Steinbrenner, Jessica R.; Odom, Samuel L.; Nowell, Sallie W.; Waters, Victoria; Perkins, Yolanda; White, Mary; Swaminathan, Hariharan; Rogers, H. Jane
The purpose of this study was to examine the efficacy of a teacher-implemented professional development program to increase the fidelity with which paraeducators use evidence-based practices (EBPs) in instruction for children with autism. Employing a modified multiple-probe design, investigators implemented the Autism Focused Intervention Resources and Modules for Paraprofessionals (AFP) program in four special education and four inclusive classrooms enrolling students with autism. As the teacher initiated features of the AFP program focusing on individual EBPs, level changes in paraeducators' EBP fidelity increased markedly, with replications across paraeducators demonstrating experimental control. Statistical analyses produced large effect sizes, Goal Attainment Scale scores indicated student progress, and participants' ratings reflected strong social validity. School closure due to the COVID-19 pandemic prevented the completion of the study, but the pattern of effects suggests the efficacy of the AFP program as a program of professional development for paraeducators providing instruction for children with autism.